2019
DOI: 10.1103/physrevb.100.125106
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic energy density of nearly free electrons. I. Response functionals of the external potential

Abstract: Free electrons have a uniform kinetic energy density (KED), which evolves into a spatially varying quantity as the electrons respond to the gradual imposition of an external potential. In this paper and a companion paper, we examine two sets of functionals for describing the local, non-negative KED that emerges after such a perturbation. In this paper, we emphasize potential functionals, deriving the first-and secondorder deviations from the free-electron KED as functionals of the perturbing potential, also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…However, kinetic energy functional development is an active area of research, 26 32 and numerous approximate functionals, having various desirable features, are available. 9 12 Some, like ours, enforce the T s ≥ T W constraint by construction.…”
Section: Methodsmentioning
confidence: 99%
“…However, kinetic energy functional development is an active area of research, 26 32 and numerous approximate functionals, having various desirable features, are available. 9 12 Some, like ours, enforce the T s ≥ T W constraint by construction.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we have used the variables in Eqs. (16), (17) and the approximate relationship Eq. (21) between F τ and F σ .…”
Section: B Adaptation To Pseudo-densitiesmentioning
confidence: 99%
“…Both semilocal and non-local functionals have achieved mixed successe in treating condensed phases and their ingredient atoms, molecules, and clusters and solids. Such functionals are either constraint-based and non-empirical [8][9][10][11][12][13][14][15][16][17][18] or semi-empirical 19,20 . With any significant ground-state advance, an obvious, important associated step is generalization to a non-interacting free energy functional F s .…”
mentioning
confidence: 99%
“…33,36,37 On the other hand, the parameter range corresponding to densities r s 2 and temperatures 0.01 θ < 1 is highly important for numerous applications. For example, recently it was shown that the static non-linear density response functions of the electron gas can be used for the construction of advanced kinetic energy functionals required for orbital-free density functional theory (OF-DFT) based simulations 38,39 with applications at ambient 40 as well as extreme conditions. 41,42 Additionally, non-linear density response functions can extend quantum fluid models (quantum hydrodynamics and time-dependent orbital-free density functional theory) beyond the weak perturbation regime.…”
Section: Introductionmentioning
confidence: 99%